A study of the relationship between gesture and intonation in public speaking / Moh Jun Han - Moh , Jun Han (2017)
Public speaking is an important skill for a person to master if he or she wants to be an effective communicator. Previous studies have investigated the relationship between speech and gesture and it was found that they enhance speakers’ verbal delivery and listeners’ understanding of the speech (Driskell and Radke, 2003). However, most of these studies only focused on natural speech between small groups of people or between researchers and their respondents. Moreover, these studies also mostly studied gesture and intonation separately. This study aims to investigate the relationship between gesture and intonation in public speaking. The introductory segments of four speeches which were crafted and delivered by the winners of the Toastmasters World Championship of Public Speaking were selected for this study. The videos of the selected segments of the speech were annotated using Elan and Praat. The gestures of the speakers were first annotated in Elan using Kendon’s (1972) hierarchy of gestures as the analytical framework to code the gestures. The intonation of the same segments was measured and annotated in Praat using the Tone and Break Indices (ToBI) framework developed by Beckman and Elam (1997). Previous studies like Loehr’s (2004) have generalised that pitch accents are always aligned with the ‘apex’ of a gesture in natural speech. However, the findings in the current study indicate that pitch accents in public speech are not only aligned consistently with the stroke of a gesture, but that they also occur during the post-stroke hold phrase and even when there is no gesture at all. In addition, the findings also show that a pitch accent, stroke and post-stroke hold phrase also tend to coincide more with a content word compared to a function word. Furthermore, the function words which were aligned with pitch accents also tend to be first person pronouns, confirming and expanding upon previous work. Overall, the findings seem to suggest that although gesture and intonation play various roles in public speaking, the prosodic elements of a speech seem to have a bigger influence on the quality of a speech.